0862 Does Napping for Headache Relief Lead to Sleep Disturbance at Night?. (12th April 2019) - Dawson, Spencer C; Burgess, Helen J; Wyatt, James K; Hedeker, Donald; Park, Margaret; Rains, Jeanetta C; Espie, Colin A; Taylor, Hannah L; Ong, Jason C
Abstract: Introduction: Compensatory sleep behaviors (e.g., naps, going to bed earlier) are often used to cope with headaches. However, it is not known if these coping behaviors lead to subsequent disturbances in nocturnal sleep. We tested this hypothesis by examining the temporal relationships between headaches, daytime naps, and nocturnal sleep in women with chronic migraines. Methods: Twenty women with chronic migraine (Mean age = 32.2) and 20 age-matched female controls (mean age = 31.7) completed daily diaries on nocturnal sleep, daytime naps, and headache severity ratings (0-10, severity > 2 classified as headache) for approximately one month (M=28.20 days, range=21-36). T-tests were conducted to compare groups and linear mixed models were used to examine temporal relationships within the migraine group. Results: Compared to controls, participants with migraines napped more often (28.54% of days vs 7.25%, p=.0113) and had worse subjective sleep including longer sleep onset latency (SOL; 29.11 minutes vs 10.15, p=.0015) and lower subjective sleep efficiency (SE; 80.39% vs 90.98%, p=.0002). Within the migraine group, headache severity predicted taking a nap (p=.0236), taking longer naps (p=.0003) and an earlier nocturnal bed time (BT; p=.0171) on the same day. Napping predicted longer SOL (p=.0244) and earlier BT predicted lower SE (p=.0038) and longer total sleep time (TST; p<.0001), but did not predict SOL (p=.2815). Longer TST was associated with lower likelihood of next-day headache (p=.0444) but no significant relationship was found between SOL (p=.4363) or SE (p=.1973) and next-day headache. Conclusion: The results support the hypothesis that using naps and an earlier bedtime to cope with headaches would be associated with nocturnal sleep disturbance. Interestingly, going to bed earlier was also associated with longer nocturnal sleep, which was associated with lower likelihood of next-day headache. These findings provide novel insights into the use of compensatory sleep behaviors to cope with headache pain which could serve as a precipitating factor for comorbid insomnia. Support (If Any): This study was supported by grant R21NS081088 from the National Institutes of Health.